Оцінка невизначеності вимірювань при калібруванні мірників еталонних - Новосьолов, О. А. (ХНУРЕ, 2024)
The problem of calibration of working standards used during the verification of measuring equipment, which are in operation and used in the field of legally regulated metrology, is considered. The procedure for estimating the uncertainty of measurements when calibrating a standard 2-digit meter using the volumetric method is described - recording the measurement model, estimating the input and measured values, estimating the standard uncertainties of the input and measured values, and estimating the extended uncertainty. The measurement uncertainty budget was drawn up.
Keywords: калібрування мірників еталонних; оцінка невизначеності вимірювань